ChemInform Abstract: Synthesis and in vitro and in vivo Anticancer Activity of Novel 3‐Methyl‐5H‐isoxazolo[5′, 4′:5, 6]pyrido[2, 3‐b]indoles. Issue 12 (14th March 2013) - Rajanarendar, E.; Reddy, K. Govardhan; Ramakrishna, S.; Reddy, M. Nagi; Shireesha, B.; Durgaiah, G.; Reddy, Y. N.
Abstract The in vivo and in vitro screening of the title compounds (IV) (8 examples) for their anticancer activities shows that compounds (IVb) and (IVd) exhibit potential anticancer activities as compared with the reference compound Cisplatin.